THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLES ON EMPLOYE PERFORMANCE THRU JOB SATISFACTION AT KPP PERTAMA BANDAR LAMPUNG DUA - Fahmi Syuhada; Riswan (PT. Hasba Edukasi Mandiri, 2026)
This research employed a quantitative approach using a survey method. The population consisted of all employees of KPP Pratama Bandar Lampung Dua, with a sample of 72 respondents selected through simple random sampling. Data were collected using questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software. The empirical findings demonstrate that transformational and transactional leadership each exert a positive and statistically significant influence on employee performance and job satisfaction. Furthermore, job satisfaction contributes positively and significantly to employee performance and functions as a significant mediating mechanism in the association between transformational leadership and employee performance, as well as between transactional leadership and employee performance. Thus, all research hypotheses were accepted. The findings conclude that improving employee performance can be achieved through the effective implementation of transformational and transactional leadership styles, both directly and indirectly through enhanced job satisfaction as a mediating variable. Therefore, KPP Pratama Bandar Lampung Dua is recommended to strengthen leadership competencies, improve its reward system, foster effective organizational communication, and create a work environment that enhances employee job satisfaction. Future studies are recommended to broaden the analytical framework by incorporating other factors that may contribute to employee performance, including work motivation, organizational culture, organizational commitment, and employee engagement. Furthermore, extending the research scope to encompass different organizational contexts and settings may provide a more comprehensive understanding of the determinants of employee performance and enhance the generalizability of the findings.